Design of a canal system for the North Vamnao Project - To Quoc Dung; Jensen, Niels Einar; Loof, Rainer; Harboe, Ricardo; Federal Republic of Germany (DAAD) (Bangkok : Asian Institute of Technology, 1990)
This study deals with the design of an irrigation and drainage system for the North vamnao area, location in the tidal zone of the lower mekong river. Three possible alternatives are suggested for the design, then the system which has the best maximum net benefits and whose costs of construction are acceptable for implementation is then selected. Alternatives based on critical analysis of the physical constraints, present situation, socio-economical consideration and possible future developments are suggested. The CROPWAT package is used for calculating the water requirement and MIKE 11 is used for the design dimensions of the main canal system. Firstly, the MIKE 11 was used to calibrate the flow in the existing channel system, which covers a large area, then to generate water levels around the project. Secondly, the generated water levels are used as boundary conditions for a smaller model (the so-called model 2) to design canal dimensions for the different alternatives. A Combined irrigation and drainage system is recommended for implementation, with a benefit/cost ratio of 3.57 and internal rate of return of 48.1% according to a discount rate of 10%. Within this project, all waste land is exploited and crop circle is increased leading to a higher net benefit.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1990
Keywords: North Vamnao Project; Canals -- Vietnam -- Vamnao River -- Design and construction